2022
DOI: 10.1101/2022.04.15.488525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CbpD crystal structure adds intrigue to substrate-specificity motifs in chitin-active lytic polysaccharide monooxygenases

Abstract: Pseudomonas aeruginosa secretes diverse proteins via its Type 2 Secretion System, including a 39 KDa Chitin-Binding Protein, CbpD. CbpD was recently shown to be a lytic polysaccharide monooxygenase active on chitin, and to contribute substantially to virulence. To-date no structure of this virulence factor has been reported. Its first two domains are homologous to those found in the crystal structure of Vibrio cholerae GbpA, while the third domain is homologous to the NMR structure of the Cellvibrio japonicus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
(206 reference statements)
0
1
0
Order By: Relevance
“…Currently, increasing LPMOs are found to have multiple conserved domains, which play an essential role in the substrate binding and catalytic efficiency of LPMOs (Courtade and Aachmann, 2019;Mekasha et al, 2020). In addition, some domains may also protect LPMOs from autocatalytic inactivation (Dade et al, 2022). The analysis of conserved domains showed that M2822 contained four conserved domains (Figure 3C).…”
Section: Phylogenetic Analysis Sequence Comparative Analysis and Stru...mentioning
confidence: 99%
“…Currently, increasing LPMOs are found to have multiple conserved domains, which play an essential role in the substrate binding and catalytic efficiency of LPMOs (Courtade and Aachmann, 2019;Mekasha et al, 2020). In addition, some domains may also protect LPMOs from autocatalytic inactivation (Dade et al, 2022). The analysis of conserved domains showed that M2822 contained four conserved domains (Figure 3C).…”
Section: Phylogenetic Analysis Sequence Comparative Analysis and Stru...mentioning
confidence: 99%